Current concept of treating female genital tuberculosis - Santos Astete, Alberto (2015)
In 2504 patients from "Hospital Loayza" (Pab. V. II Sala. Lima) since 1951 to 1956, it was 39 cases of genital tuberculous. The greatest incidence is in between 20 and 30 years and should be localized: Fallopian Tubes, 100%. Endometrium, 51%. Ovary, 24%. Myometrium. 10%. Uterine Cervix, 10%. Peritoneal extension, 10%. The Endometrial Biopsy was admitting of no doubt in 66% of the cases. The greatest accuracy in the diagnosis could be possible wit the use of the hysterosalpingography with or without other methods. The use of antibiotics and chemotherapy changed the prognosis and the measure treatment.